2006
DOI: 10.3310/hta10080
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Barrett's oesophagus: exploring the uncertainty through systematic review, expert workshop and economic modelling

Abstract: The systematic review concludes that there is insufficient evidence available to assess the clinical effectiveness of surveillance programmes of Barrett's oesophagus. There are numerous gaps in the evidence, of which the lack of RCT data is the major one. The expert workshop reflected these gaps in the range of topics raised as important in answering the question of the effectiveness of surveillance. Previous models of cost-effectiveness have most recently shown that surveillance programmes either do more harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 41 publications
(138 reference statements)
1
94
0
3
Order By: Relevance
“…To date, we know of no randomized controlled trials of BE surveillance that have been published; however, several authors have used mathematical models to explore the costeffectiveness of surveillance [158][159][160]. Despite different modeling approaches and the application of different costs, these studies confirm that the cost-effectiveness of surveillance is crucially dependent on the incidence of EAC.…”
Section: Surveillance Of Be and Perspectivesmentioning
confidence: 81%
See 1 more Smart Citation
“…To date, we know of no randomized controlled trials of BE surveillance that have been published; however, several authors have used mathematical models to explore the costeffectiveness of surveillance [158][159][160]. Despite different modeling approaches and the application of different costs, these studies confirm that the cost-effectiveness of surveillance is crucially dependent on the incidence of EAC.…”
Section: Surveillance Of Be and Perspectivesmentioning
confidence: 81%
“…On the basis of costs in the USA, Provenzale et al [158] concluded that, for a cancer risk of 5 per 1,000 pyrs, surveillance every 4 years was indicated and, if the risk was 0.4 percent per year, surveillance every 5 years was the only strategy to increase a patient's quality of life. With regard to modeling surveillance from a UK perspective, Garside et al [160] concluded that, at a cancer risk equivalent to 0.5 percent per year, no surveillance costs less and results in a better quality of life than surveillance, irrespective of the surveillance interval used. The estimates of cancer incidence obtained from this systematic review are close to those used in these models and clearly indicate that the cost-effectiveness of Barrett's surveillance is questionable unless it can be targeted to those BE patients who are at the highest risk of cancer.…”
Section: Surveillance Of Be and Perspectivesmentioning
confidence: 99%
“…This has been a particularly contentious topic with health economic studies producing mixed results as to the cost-effectiveness of endoscopic surveillance of Barrett's esophagus [5]. In 2009 two US studies recorded mean costs per patient under surveillance of $2,769 [31] and $11,532 [32] for surveillance programs involving 5-yearly screening intervals, and $7,940 was reported for one UK study with 3-yearly intervals (converted to $ 2009) [13]. Our cost cut-off of $4971 per patient within an early detection program appears to be in the overall range of these costs.…”
Section: Discussionmentioning
confidence: 99%
“…Australian life-tables provided information on background all-cause mortality [11]. Utility scores to adjust survival estimates in estimating quality-adjusted life years were obtained from a literature review on utility weights for treatments for esophageal adenocarcinoma [12][13][14][15]. Table 1 …”
Section: Data Sourcesmentioning
confidence: 99%
“…The inclusion of VoI as a part of health economic evaluations is increasing [3][4][5][6][7][8][9][10][11][12]. This is useful to direct future research effort to where it can achieve the greatest expected return for finite funding.…”
Section: Introductionmentioning
confidence: 99%